Estimation of Carbon Emissions of Domestic Energy Usage by Chinese Residents Based on Input - Output Method - Sheng Zhonglin; Gu Kan; He Weida (E3S Web of Conferences, 2018)
This paper will be based on the existing literature and research methods, with the 1980 to 2014 China’s residential carbon emissions estimates. This paper mainly examines the changes in total residential carbon emissions and per capita carbon emissions, energy consumption per unit of household energy consumption, carbon emissions and energy composition of the above-mentioned analysis of urban and rural compared with the international comparison.